2016
DOI: 10.3892/ijmm.2016.2677
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic changes in human renal proximal tubular cells revealed under hypoxic conditions by RNA sequencing

Abstract: Chronic hypoxia often occurs among patients with chronic kidney disease (CKD). Renal proximal tubular cells may be the primary target of a hypoxic insult. However, the underlying transcriptional mechanisms remain undefined. In this study, we revealed the global changes in gene expression in HK‑2 human renal proximal tubular cells under hypoxic and normoxic conditions. We analyzed the transcriptome of HK‑2 cells exposed to hypoxia for 24 h using RNA sequencing. A total of 279 differentially expressed genes was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…51). HIF-1␣ has also been reported to be elevated in 1% O 2 milieu, specifically in proximal tubular cells (10,31,58). In line with the literature, we found that hypoxia led to a robust HIF-1␣ increment and translocation to the nucleus of proximal tubular cells.…”
Section: Dapa Diminishes Elevated Protein O-glcnacylation In the Kidnsupporting
confidence: 91%
“…51). HIF-1␣ has also been reported to be elevated in 1% O 2 milieu, specifically in proximal tubular cells (10,31,58). In line with the literature, we found that hypoxia led to a robust HIF-1␣ increment and translocation to the nucleus of proximal tubular cells.…”
Section: Dapa Diminishes Elevated Protein O-glcnacylation In the Kidnsupporting
confidence: 91%
“…The human kidney contains epithelial cells in the proximal tubules (HK‐2) that require high concentrations of O 2 to maintain their metabolic functions; therefore, in hypoxic conditions, the activation of antiregulatory mechanisms is initiated to adapt to decreased bioavailability of O 2 . Yu et al, aiming to elucidate the mechanisms involved in renal proximal tubule cells, performed a transcriptome analysis in this cell type. They identified an increased expression in 201 genes, all of which are associated with hypoxia and extracellular matrix deposition (ECM) such as TGF‐β1, VEGF, 6‐phosphofructo‐2‐kinase/fructose‐2,6‐bisphosphatase 4 enzyme (PFKFB4), GLUT1, HIF‐1α, and Collagen IV and found that a hypoxic environment induces increased HIF‐1α expression and exacerbates CKD, besides favouring tumorigenesis.…”
Section: Discussionmentioning
confidence: 97%
“…There are some divergences in literature on the relationship between HIF and other genes involved on the installation of renal dysfunction. VEGF, GLUT1, and TGF‐β1 have been described as coexpressed genes under renal failure conditions; according to these studies, these markers may interact directly with the expression of HIF …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A critical limitation of transcriptomic analysis is that it cannot establish a causal relationship between expression of genes and disease development [16]. While some genes and pathways are involved in disease development, others are mostly just a consequence of the disease state [41,42]. As genotype assortment always occurs prior to disease development, genotype information can help to identify causal genetic pathways [43].…”
Section: Genetically Driven Gene Expression Changesmentioning
confidence: 99%